Applied study for general inhalation anaesthesia in sheep - A., Mohannad S.; A., Nabih M.; J., Ayad A. (The Iraqi Journal of Veterinary Medicine, 2001)
General inhalation anaesthesia has been evaluated in twelve local sheep, which were divided in two equal groups. First group anaesthtized by induction with intravenous injection of ( Atropine sulfate 0.4 mg/kg B.W) and after 10 to minuts ( xylazine 0.02 mg/kg . B.W.) and ( Ketamine 10 mg/kg . B.W.). While the second group has been inducted with ( xylazine 0.02 and pentobarbiton sodium 15 mg /kg B.W) with intravenons injection premidirated with (Atropine sulfate 0.4 mg/kg B.W). The general anaesthesia has been maintained in both groups with inhalation of halothane and oxygen 1-2% concentration by (( To and Fro)) inhalation closed system. The changes in the parameters of pulse rate, respiratory rate, rectal temperature and ruminal contractions has been considered from time 0 to 60 minutes to evalute the general anaesthesia .xylazine and ketamine induction followed with halothane show effective and safe gerenal anaesthesia with excellent muscle relaxation , analgesia and ensured rapid and safe recovery with minium cardio-pulmonary depression .